(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article is devoted to the expression of national culture, traditions and manners with the use of non-verbal means in interpersonal communication in Uzbek and Russian languages. In this article traditions are described in these four languages. Non-verbal means in communication are divided into different groups circumstances of usage, purpose, interaction, content. The article also summarizes the opinions and theoretical views of Uzbek and Russian scientists on non-verbal means of communication, information and materials collected on this issue, as well as a comparative analysis and clarification of their content. In particular, it was proved by examples that verbal and non-verbal means are used synchronically, which makes the speaker’s speech more understandable, interesting and attractive and less physically requiring. Moreover, it was studied that the same simultaneous actions or gestures of people can serve as a component of non-verbal communication in the process of interaction.